Emulsifying properties of legume proteins compared to beta-lactoglobulin and Tween 20 and the volatile release from oil-in-water emulsions - Benjamin, Ofir; Silcock, Patrick; Beauchamp, Jonathan; Büttner, Andrea; Everett, David W. (Journal of Food Science, 2014)
The emulsifying properties of plant legume protein isolates (soy, pea, and lupin) were compared to a milk whey protein, β-lactoglobulin (β-lg), and a nonionic surfactant (Tween 20). The protein fractional composition was characterized using sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis. The following emulsion properties were measured: particle diameter, shear surface ζ-potential, interfacial tension (IT), and creaming velocity. The effect of protein preheat treatment (90 °C for 10 min) on the emulsifying behavior and the release of selected volatile organic compounds (VOCs) from emulsions under oral conditions was also investigated in real time using proton transfer reaction-mass spectrometry. The legume proteins showed comparable results to β-lg and Tween 20, forming stable, negatively charged emulsions with particle diameter d3,2 < 0.4 μm, and maintained stability over 50 d. The relatively lower stability of lupin emulsions was significantly correlated with the low protein surface hydrophobicity and IT of the emulsion. After heating the proteins, the droplet size of pea and lupin emulsions decreased. The VOC release profile was similar between the protein-stabilized emulsions, and greater retention was observed for Tween 20-stabilized emulsions. This study demonstrates the potential application of legume proteins as alternative emulsifiers to milk proteins in emulsion products.
UnivIS-Import:2015-07-08:Pub.2014.nat.dchph.llmch.emulsi
Keywords: Emulsifying properties; Heat treatment; Legume proteins; Volatile release; β-lactoglobulin